The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.35335/enrichment.v12i6.1124
|View full text |Cite
|
Sign up to set email alerts
|

The effect of digital literacy and transformational leadership on employee performance mediated by innovative work behavior at the Padang city population and civil registration service

Abstract: This study aims to see the effect of digital literacy and transformational leadership on employee performance with innovative work behavior as a mediating variable. Research conducted on Department of Population and Civil Registration of the City of Padang. The population in this study were all employees of the state civil apparatus (ASN) and non-state civil servants (Non ASN) of the Padang City Population and Civil Registration Service. The sample collection technique is a saturated sample, that is the entire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
(15 reference statements)
1
2
0
Order By: Relevance
“…It means that digital literacy is a reasonable proclivity for teachers to have to improve their professional performance. These findings are consistent with and confirm the results of previous studies, which suggest that digital literacy has a significant relationship with teachers' professional performance [4,5,[42][43][44][45][46]. Consequently, teachers need to increase their digital literacy to have greater opportunities to improve their professional performance.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It means that digital literacy is a reasonable proclivity for teachers to have to improve their professional performance. These findings are consistent with and confirm the results of previous studies, which suggest that digital literacy has a significant relationship with teachers' professional performance [4,5,[42][43][44][45][46]. Consequently, teachers need to increase their digital literacy to have greater opportunities to improve their professional performance.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, when teachers have an adequate (high) level of digital literacy, including digital competence, usage, and transformation, it can drive their professional performance. Several prior studies also indicated that digital literacy is related to teachers' professional performance [4,5,[42][43][44][45][46]. Therefore, we can propose the first hypothesis (H): H1: Digital literacy directly relates to teachers' professional performance.…”
Section: Digital Literacy and Professional Performancementioning
confidence: 89%
See 1 more Smart Citation